Spolni stereotipi v treh slovanskih romanih: Filio ni doma, Kot da me ni in Temna ljubezen - Zupan Sosič, Alojzija (Jezik in slovstvo, 2022)
The present research of gender stereotypes in three Slavic novels is twofold. The first part presents gender stereotypes, while the second deals with their analysis and interpretation in the following nov-els: Filio Is Not At Home by Berta Bojetu, As If I Were Not by Slavenka Drakulić and Dark Love by Alexandra Berková. The study showed that the key categories for the modern approach to gender stereotypes are androgyny, phantasm, performance and criticism of misogyny, while for gender stere-otypes in the discussed novels, the global gender stereotype is fatal: a man is the head and a woman is the heart. Its danger in Filio Is Not At Home is recognised as an anti-utopian means of depersonalising people, in As If I Were Not as a confirmation of the aggressive male-centred principle, while in Dark Love stereotypical sexual socialisation is condemned as a perverse ideology of (male) violence through the following stereotypes: female caregiver, woman-servant to man and child, woman-admirer of man and man-master.
Keywords: Berková, Alexandra; Bojetu, Berta; domestication of women; domestifikacija žensk; Drakulić, Slavenka; gender stereotypes; masculinity; moškosrediščnost; sexual socialisation; Slavic literature; Slavic novels; slovanska književnost; slovanski romani; spolna socializacija; spolni stereotipi